The Trend of The Returns to Educations in Indonesia - Nenny Hendajany; Tri Widodo; Eny Sulistyaningrum (Muhammadiyah University Press, 2016)
This paper describes the rate of return to education in Indonesia. The purpose of this paper was to determine how the trend of return to education from 1993 to 2007. By using Mincer equation, we analyzed return to education in Indonesia with using Indonesia Family Life Survey (IFLS) data collected in 1993, 1997, 2000, and 2007. Mincer specification linked between income and education. Income used in this paper was real income of a person who works. The estimation of the rate of return to education started by separating each year data. Then, it used pool data by adding year variable and multiplication variable between year and education. Estimation was also carried out by comparing between men and women. Further, estimation was divided into two age cohorts, young cohort and old cohort. All the results of estimation indicated a decreasing rate of return, the greatest decrease occurred on men with old cohort.Keywords: education, return to education, Mincer equation, trendJEL codes: I26, J30